Getting started in jail, prison, and legal system research. Issue 1 (5th December 2022) - Glenn, Jason; Wickliffe, Joi; Kelly, Patricia J.
Abstract: Extensive health inequities exist for persons with criminal-legal involvement in the USA. Researchers, both novice and experienced, are critical in documenting these inequities and implementing programs that address the many health and social problems of this population. However, working with currently or formerly incarcerated persons brings new challenges to researchers that may have not been previously considered as necessary. Because incarcerated persons were systemically exploited by biomedical researchers until reform following the Civil Rights Movement, resulting in their designation as a vulnerable population in the Code of Federal Regulations, enhanced protections are necessary in implementing contemporary research involving incarcerated persons. These enhanced protections can delay or prolong the regulatory approval process, particularly to the novice carceral system researcher, which may discourage some from engaging with this important population. Drawing on the many years of experience working with incarcerated persons accumulated by the Sexual Health Empowerment (S)HE Team at the University of Kansas Medical Center (KUMC), this article offers some concrete steps toward getting started in this work.